2019
DOI: 10.3390/ma12213463
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of 1 × 7 Steel Wire Strand under Fretting Fatigue Condition

Abstract: Wire ropes undergo a fretting fatigue condition when subjected to axial and bending loads. The fretting behavior of wires are classified as line contact and trellis point of contact. The experimental study on the fatigue of wire ropes indicates that most of the failure occurs due to high localized stresses at trellis point of contact. A continuum damage mechanics approach was previously proposed to estimate the fatigue life estimation of wire ropes. The approach majorly depends on the high value of localized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…29 In the wire ropes, trellis points of contact have a central role in fatigue life at which the stresses are high along with slip at the annulus region of the contact spot. 65,66 The subroutine developed and implemented F I G U R E 1 3 Experimental marks for the fretting fatigue in the annulus region of contact of steel wire ropes. 29 here for the wire-on-wire model will be implemented on wire rope in the future.…”
Section: Friction Coefficientmentioning
confidence: 99%
“…29 In the wire ropes, trellis points of contact have a central role in fatigue life at which the stresses are high along with slip at the annulus region of the contact spot. 65,66 The subroutine developed and implemented F I G U R E 1 3 Experimental marks for the fretting fatigue in the annulus region of contact of steel wire ropes. 29 here for the wire-on-wire model will be implemented on wire rope in the future.…”
Section: Friction Coefficientmentioning
confidence: 99%
“…They proposed that Manson's method and medians method gave lives closer to those obtained from fretting wear tests in steel wires, and the life reduction is attributed to the increase in normal contact load. Ahmad et al [6] calculated stress distributions and relative displacements of strand wires under fretting fatigue condition. They found that the relative movement occurred at the boundaries of the contact region in the presence of friction, and the existence of slip was due to different displacements of outer and central wires.…”
Section: Introductionmentioning
confidence: 99%